2018
DOI: 10.1103/physrevd.97.106012
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic safety of gravity with matter

Abstract: We study the asymptotic safety conjecture for quantum gravity in the presence of matter fields. A general line of reasoning is put forward explaining why gravitons dominate the high-energy behavior, largely independently of the matter fields as long as these remain sufficiently weakly coupled. Our considerations are put to work for gravity coupled to Yang-Mills theories with the help of the functional renormalization group. In an expansion about flat backgrounds, explicit results for beta functions, fixed poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
173
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(175 citation statements)
references
References 121 publications
(202 reference statements)
2
173
0
Order By: Relevance
“…This indicates that our analysis provides the first study of the gravity-matter fixed point identified in [12,31,83,100] at the level of self-consistent form factors. Comparing the critical exponents (112) and (113) furthermore suggests that the properties of the fixed point are essentially determined by the gravitational contributions [100]. Including a self-consistent form factor in the scalar sector has a very mild effect on the stability coefficients.…”
Section: Resultsmentioning
confidence: 93%
“…This indicates that our analysis provides the first study of the gravity-matter fixed point identified in [12,31,83,100] at the level of self-consistent form factors. Comparing the critical exponents (112) and (113) furthermore suggests that the properties of the fixed point are essentially determined by the gravitational contributions [100]. Including a self-consistent form factor in the scalar sector has a very mild effect on the stability coefficients.…”
Section: Resultsmentioning
confidence: 93%
“…Typical values of f g are of the order O(10 −2 ) [41] and here we use f g ≤ 0.04. Gravity supports asymptotic freedom for non-abelian gauge theories and the gauge couplings run in the Gaußian fixed point g * = 0 [64,66]. This Gaußian fixed point is relevant and thus the gauge couplings approach it slowly beyond the Planck scale.…”
Section: B Gauge Couplingmentioning
confidence: 89%
“…Again,G = Gµ 2 andΛ = Λ/µ 2 are the dimensionless versions of the Newton coupling and cosmological constant. Importantly, f g is positive for all relevant values of the gravity couplings, see [66], which makes the contribution to the beta function negative. Typical values of f g are of the order O(10 −2 ) [41] and here we use f g ≤ 0.04.…”
Section: B Gauge Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…For some recent work on AS, see Refs [13][14][15],. and for references to work up to 2017, see Ref [16].…”
mentioning
confidence: 99%